(untitled) (Fiep Bulletin - online, 2015)
The incorrect handling of heavy loads with the own body is the generating cause of two main kinds of pains in workers around the world, but specifically backache or low back pain, which holds the second biggest amount of people suffering from it, being the first the headache. In this paper, the ergonomics issue inside a CEASA (Supply Center) in the South of Brazil was analyzed, collecting attitudes adopted by workers, such as their main complaints related to muscular pains, caused by their workdays. For this, several visits to CEASA were necessary, in order to keep up with the routine of the workers, and a questionnaire was applied with ergonomics focus, to know more about workers involved with handling and moving of loads. The outcomes of the visits showed that these workers move and lift much more load than what it would be coherent during the work expedient, as well as it showed that the main complaints of the workers were about backache and leg pain, which can be generated not only by inadequate stance while moving and lifting products, but also by the huge load handled. It follows that the ergonomics situation analyzed inside CEASA is fully unfavorable to the interviewed worker’s health, and still awareness behaviors about good ergonomics practices (such as stretching) are vital for them to work in a less painful way.